Management control systems and strategy: A resource based perspective. Evidence from Greece - Nikolaos Theriou; Dimitrios Maditinos; Georgios N. Theriou (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The purpose of this paper is to empirically examine from the resource-based perspective, the relationship between the use of management control systems (MCS) and organisational capabilities in the Greek context. Design/Methodology/Approach: The study follows Henri's (2006) methodology and explores the relationships between the diagnostic and interactive uses of performance measurement systems (PMS) and the five capabilities (e.g. market orientation, organisational learning, entrepreneurship, innovativeness and market responsiveness) leading to strategic choice. Structural equation modelling represents the relationships between the variables and data collected from the survey, which was analysed as a statistical tool with AMOS. Findings: Results revealed that diagnostic use of PMS negatively influence only the organisational learning, while the interactive use positively interacts with most of the capabilities. Research limitations/implications - This study can be further extended by incorporating more factors in the proposed model, such as environmental uncertainty, size and organisational culture, and examine their possible effect on the relationship between PMS uses, organisational capabilities and performance. Originality/Value: There is no similar empirical research in the context of Greece.
Keywords: M49; M19; 330; Management Control Systems (MCS); Strategy; Capabilities; Business Performance; Confirmatory Factor Analysis and Structural Equation Modelling